Sampan Sudur Sungai Padang, Temuan Arkeologis di Tanjungmarulak, Tebingtinggi, Sumatera Utara - Lucas Partanda Koestoro (Berkala Arkeologi Sangkhakala, 2007)
AbstractThe finding of a dugout canoe in Sungai Padang, Tebingtinggi add the data of existence means of transportation from time to time coastal area of east Sumatera Island. Known as sampan sudur, this simple boat type is popular enough, its use at past and that with reference to Tebingtinggi at 19 th century, shares a institution of governance of Kedatukan Padang, which is under influence of the reign of Sultanate Deli.